Hydrodistilled Volatile Oil from Stems of Eryngium creticum Lam. in the Marginal Brackish Regions of Semnan Province by Using Gas Chromatography Combined with Mass Spectrometry - Mohammadhosseini, Majid (Asian Journal of Chemistry, 2012)
The present report deals with chemical composition of the volatile oil from stems of Eryngium creticum Lam. a growing wild plant in Iran. All the samples were collected from different brackish and hill slope locations during the flowering stage in Semnan province, Iran. The oil was obtained by using a modified Clevenger-type apparatus and the respective analyses were performed by means of GC and GC-MS instrumentations. It was obtained as a clear yellowish colour liquid involving 0.18 w.w-1 (%). Seventeen components were identified constituting 91.4 % of the oil composition. The major components of the oil were found to be bornyl acetate (28.4 %), camphor (17.8 %), a-pinene (12.1 %), germacrene D (9.4 %), borneol (8.6 %) and a-thujene (4.2 %). Based upon the chemical profile, the essential oil was mainly characterized by the presence of higher amounts of oxygenated monoterpenes.